Design Traffic Light of HCSR04 Sensor Fuzzy Logic Method Based on Arduino Mega 2560 - Muhammad Dermawan; Selamat Meliala (International Journal of Engineering, Science and Information Technology, 2022)
Modern technology is developing quite fast. Manufacturing, consumer electronics, and traffic management are just a few everyday tasks made more accessible by various technologies. Regular traffic signals work according to a set time or hour according to one road condition. Therefore, it is essential to time traffic signals at intersections so drivers must wait for the shortest time. In this study, we explore the feasibility of modeling a control system using the fuzzy Mamdani algorithm so that the timing of traffic lights at highway intersections can be adjusted in real-time. Each element, such as the number of cars, motorbikes, and road width, plays a role in determining whether or not a traffic light is activated. It is possible to get a red light that changes adaptively in response to road conditions by conducting tests with varying parameter settings. Based on the results of testing the system as a whole, it can be determined that traffic lights can prioritize the long green density first among the four lanes if the number of cars in one of the lanes is more, and those in the fewer lanes will take precedence over the more congested roads. That system testing is booming, according to design. Battery-free toy vehicles were deployed on each track for testing. The sensor will recognize the car as an object and interpret the data sent and received by the Arduino Mega processing system. The system will then analyze the density condition and display it on the LCD and sensor data, the length of the green traffic light, and the density condition.